(untitled) (Journal of Parents and Teachers, 2014)
Today’s children are growing up in an environment that requires them to achieve certain grades and leads to rivalry. Few professionals and parents are concerned that the values being reinforced are those of competitiveness and selfishness rather than those of success and quality of education. The problem lies in the productive force required by the market, i.e. it is increasingly believed that studies must be directly connected to the market in order to get a well-paid job in the future. This only contributes to the disillusionment of society. This is the case with education, which contributes to improving people’s quality of life, but not always immediately. It is therefore urgent to reconnect the school institution with the environment.